Application of Moringa Seeds Coagulant to Treat Wastewater from Chicken Slaughterhouse Industry - Nabila, Azhira Syntha; Hadisoebroto, Rositayanti; Marendra, Sheilla Megagupita Putri (Journal of Community Based Environmental Engineering and Management, 2024)
Liquid waste generated by the chicken slaughterhouse industry results in an increased concentration of organic matter decomposes in the environment. High organic matter content can be achieved by the coagulation-flocculation method. This study aims to determine the removal efficiency of turbidity, BOD, COD, and TSS in the reactor. A dose of 250 mL with a coagulation speed of 100 rpm 1 minute and a flocculation speed of 25 rpm 10 minutes with a variation of settling time of 1.5 hours, 2 hours, and 2.5 hours of moringa seeds were investigated to find reduction levels of turbidity, BOD, COD, and TSS. This study showed that moringa seed coagulants were able to reduce the BOD concentration by 87.74% with an initial level of 662 mg/L to 101.01 mg/L in 2.5 hours, a COD concentration of 61.43% with an initial level of 2240 mg/L to 864 mg/L at 2.5 hours, the TSS concentration was 77.78% with an initial level of 360 mg/L to 80 mg/L at 2.5 hours while the turbidity value was 87.73% with an initial level of 441 NTU to 54.1 NTU. Moringa seeds could be effectively used to reduce the parameters of turbidity, TSS, BOD, and COD.